2006
DOI: 10.1121/1.2258500
|View full text |Cite
|
Sign up to set email alerts
|

Effects of directional microphone and adaptive multichannel noise reduction algorithm on cochlear implant performance

Abstract: Although cochlear implant ͑CI͒ users have enjoyed good speech recognition in quiet, they still have difficulties understanding speech in noise. We conducted three experiments to determine whether a directional microphone and an adaptive multichannel noise reduction algorithm could enhance CI performance in noise and whether Speech Transmission Index ͑STI͒ can be used to predict CI performance in various acoustic and signal processing conditions. In Experiment I, CI users listened to speech in noise processed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 48 publications
1
42
0
Order By: Relevance
“…For example, Chung et al (2006) reported a 3.5 dB benefit for a hypercardioid directional over an omni-directional microphone. One source of the higher Dipole relative to Omni SRT benefit observed here might be the particular interaction of noise source location with the dipole-microphone directional response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Chung et al (2006) reported a 3.5 dB benefit for a hypercardioid directional over an omni-directional microphone. One source of the higher Dipole relative to Omni SRT benefit observed here might be the particular interaction of noise source location with the dipole-microphone directional response.…”
Section: Discussionmentioning
confidence: 99%
“…One source of the higher Dipole relative to Omni SRT benefit observed here might be the particular interaction of noise source location with the dipole-microphone directional response. Chung et al (2006) evaluated beamformers using a noise field generated by playing uncorrelated noise from 8 speakers at 0 , 45 , 90 , 135 , 180 , 225 , 270 , and 315 . In this case, no particular loudspeaker was positioned exactly at either of the theoretical free-field hypercardioid azimuthplane null locations (120 and 240 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a directional design microphones are sensitive toward sounds emanating from the front and attenuate sounds originating outside the desired pickup area (Chung, 2004;Chung et al, 2006). The Nucleus 5 CP810 device uses two closely spaced and matched omni-directional microphones (front and rear).…”
Section: Zoom Processingmentioning
confidence: 99%
“…Fixed and adaptive (software or hardware) directional microphones as well as beamforming algorithms have been extensively investigated during the past two decades [5]. In [6], an overall improvement of 3-5 dB has been reported by directional microphones in comparison to processing with omnidirectional microphones, for tests with CI users in low reverberation environments. A detailed overview of fixed and adaptive directional microphones can be found in [5].…”
Section: Introductionmentioning
confidence: 99%